FACTORS AFFECTING PARTICIPATION IN A COMMUNITY-BASED PROGRAM: PADANG CITY-WEST SUMATRA'S EXPERIENCE - Abdul Rahman, Mohd Shahril; Naumar, Afrizal; Mohammed, Abdul Hakim; Azis, Shazmin Shareena Abdul (Journal of Sustainable Technology and Applied Science (JSTAS), 2021)
Improving the quality of life of a community or an individual is an important aspect for society. This can be achieved in a number of ways that involve the participation of a number of parties. One way is through a community-based sanitation program (SANIMAS). However, community participation is another challenge that we should consider in order to ensure the success of promoting participation in a community-based program as one of the ways to improve the quality of life of society as a whole. The aim of present study is therefore to identify factors influencing community participation in a SANIMAS program. Community participation was measured in the form of frequency and quantitative descriptive distribution on the basis of the Likert scale. Findings discusses a number of internal and external factors related to community participation in the SANIMAS program. It contributes to the current literature review of various internal and external factors that promote the participation of the community in improving their quality of life. This study may be used as a reference for the Government and may be established at other locations for the development of environmental infrastructure in the context of the participation of the urban community.